2014
DOI: 10.1002/ejhf.166
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical circulatory support improves diabetic control in patients with advanced heart failure

Abstract: Aims Left ventricular assist devices (LVADs) are increasingly being used as life‐saving therapy for end‐stage advanced heart failure. Diabetes is prevalent in advanced heart failure patients. In this study, we sought to investigate the effects of mechanical circulatory support on diabetic parameters with LVAD implantation. Methods and results In this retrospective study, data on 244 LVAD recipients between 2006 and 2013 were reviewed. Patients without history of diabetes, death within the first 3 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…In our study, however, BMI did not decrease after LVAD implantation, and it even significantly increased in the last year of the study. This finding is consistent with observations of previous studies that concluded improved insulin resistance cannot be attributed to increased physical activity after LVAD implantation …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, however, BMI did not decrease after LVAD implantation, and it even significantly increased in the last year of the study. This finding is consistent with observations of previous studies that concluded improved insulin resistance cannot be attributed to increased physical activity after LVAD implantation …”
Section: Discussionsupporting
confidence: 93%
“…These changes may have a favorable effect on metabolic pathways and the clinical course of diabetes because improved glycemic control appears to follow increased end‐organ function . In particular, enhanced perfusion of the pancreas increases production and transport of insulin to the body, allowing for more efficient glucose utilization …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6,21,23 The physiologic explanation for these findings is likely multifactorial and stems from mechanical LV unloading and resultant improvements in cardiac output. To our knowledge, this is the first meta-analysis evaluating glycaemic improvement after LVAD implantations.…”
Section: Discussionmentioning
confidence: 99%